The Impact of Board Gender Diversity, Independent Commissioners, and Meeting Frequency on Financial Performance: Evidence From Indonesian Listed Bank (2019-2023) - Nabila Nurjannah; G. A. Sri Oktaryani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the impact of female representation on the board of directors, board independence, and board meeting frequency on corporate financial performance, as measured by Return on Assets (ROA). The data used in this research comes from secondary sources, namely the annual reports of IDX-listed businesses from 2019 to 2023, and a regression analysis approach applied using the Eviews 12 software. Using a purposive selection approach, 25 samples were chosen from a pool of 43 firms. Secondary sources, namely the annual reports of IDX-listed companies from 2019 to 2023, and a regression analysis method implemented in Eviews 12 software, comprise the data used in this study. From a pool of forty-three companies, 25 were selected using a purposeful selection method. The results add to our knowledge of the factors that influence the effectiveness of boards in terms of membership and structure. Firms may benefit financially and socially from more equitable and long-term economic development if this study's findings motivate them to diversify their boards of directors, particularly by increasing the number of women and independent directors.